New species of Xiphoniscus and new record of Androdeloscia escalonai (Isopoda, Scutocoxifera, Oniscidea, Philosciidae) from Brazilian Amazon - Grangeiro, Daniela C.; Souza, Leila A.; Christoffersen, Martin L. (Zootaxa, 2017)
A new species in the previously monotypic genus Xiphoniscus Vandel, 1968, X. adisi sp. nov. is described. Both X. mirabilis Vandel, 1968 from Ecuador and X. adisi sp. nov. from Brazil occur in the Amazon rainforest. The new species shows a prolonged coxal plate II drawn out caudally, an autapomorphy of Xiphoniscus. Xiphoniscus adisi sp. nov. differs from X. mirabilis mainly in the characteristics of buccal appendages and male pleopods. A diagnosis of the genus Xiphoniscus is provided. The species Androdeloscia escalonai is reported from the Brazilian Amazon for the first time.